Variability in the indument of Phaseolus vulgaris var. aborigineus (Fabaceae) - Ojeda, Fabiana S. (2013)
The indument of Phaseolus vulgaris L. var. aborigineus (Burkart) Baudet, a native bean from Argentina, potential source for improvement of cultivated varieties, was compared between different genetic lines. Seeds collected from wild, weedy forms and presumptive hybrid individuals in two distant latitudes were sown in two sites of Buenos Aires University Campus (field and greenhouse). Two type of trichomes were found, which differenciate in length and shape. The pubescence density was significantly different between wild specimens from different latitudes and between culture sites for plants of a same procedence. This character could be involved in physical defences of these plants.